1993
DOI: 10.1177/001872089303500408
|View full text |Cite
|
Sign up to set email alerts
|

Improving Auditory Warning Design: Quantifying and Predicting the Effects of Different Warning Parameters on Perceived Urgency

Abstract: The effects of four parameters (speed, fundamental frequency, repetition units, and inharmonicity) on perceived urgency were scaled using an application of Stevens's power law. From the exponents obtained, equal units of urgency change were calculated for three parameters. The units were combined in a set of stimuli, and the order of urgency was predicted. The obtained and predicted orders of urgency were highly correlated. The results also showed that even when equalized by psychophysical techniques, some par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
120
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(138 citation statements)
references
References 6 publications
18
120
0
Order By: Relevance
“…For example, it is possible to calculate the am ount of change in a param eter to produce a 50% increase, a doubling, and a tripling in the perceived urgency. In practical terms, it is also im portant to be able to equate changes in urgency across different param eters as Hellier et al (1993) pointed out. Such inform ation could be used to create sets of warnings that communicate the same level of urgency through different parameters.…”
Section: Resultsmentioning
confidence: 99%
“…For example, it is possible to calculate the am ount of change in a param eter to produce a 50% increase, a doubling, and a tripling in the perceived urgency. In practical terms, it is also im portant to be able to equate changes in urgency across different param eters as Hellier et al (1993) pointed out. Such inform ation could be used to create sets of warnings that communicate the same level of urgency through different parameters.…”
Section: Resultsmentioning
confidence: 99%
“…The sound characteristics included the sonic urgency of the collision avoidance warning (defined by varying the burst density and loudness) and of the e-mail alert (defined by varying the onset and offset rates). Sonic urgency refers to the urgency of the sound based on the sound parameters that previous research has shown to influence perceived urgency as measured by subjective ratings or reaction time to warnings (Edworthy et al 1991, Hellier et al 1993, Edworthy and Adams 1996, Marshall et al 2001. In this paper, we refer to sonic urgency as 'urgency' and perceived urgency as referred to as 'rated urgency'.…”
Section: Independent and Dependent Variablesmentioning
confidence: 99%
“…Another factor that might contribute to this expected pattern of more underestimation (i.e., earlier judgments) in response to higher-frequency components is the association of higher frequencies with greater urgency (Edworthy, Loxley, & Dennis, 1991;Hellier, Edworthy, & Dennis, 1993;Russo & Jones, 2007;Russo, Lantz, English, & Cuddy, 2003). To clarify how urgency might affect judgments, it is important to consider the typical responses to TTA stimuli.…”
mentioning
confidence: 99%